Fikih Lingkungan dalam Al-Quran: Analisis Pemikiran Thahir Ibn Asyur terhadap Qs. Ar-Rum Ayat 41 - Maulidya Mora Matondang; Faisar Ananda; M. Iqbal Irham; Dhiauddin Tanjung (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Environmental destruction is a frequently discussed theme in the Quran, one of which is found in Surah Ar-Rum verse 41. This verse attracted the attention of Tahir Ibn 'Ashur, a 20th-century exegete, in his commentary Tahrir wa Tanwir. This study aims to analyze Ibn 'Ashur's thoughts on this verse and its relation to environmental jurisprudence. This research is library research with an environmental jurisprudence approach. The primary source is Tafsir al-Tahrir wa al-Tanwir, while secondary sources include the commentaries of al-Qurthubi, Ibn Kathir, as well as lexicons and environmental jurisprudence books. The findings show that Ibn 'Ashur provides a more contextual interpretation of Ar-Rum 41, particularly regarding the meaning of the term fasād. He distinguishes fasād into two meanings: a general meaning (ideological, moral, and spiritual destruction) and a specific meaning (environmental pollution). Ibn 'Ashur also affirms the causality between human actions and environmental damage, explaining the impacts on land (loss of food, plagues) and sea (decline of fish, pearls, and storms). In conclusion, Ibn 'Ashur's thought is relevant to addressing the contemporary ecological crisis as it encompasses both spiritual and material dimensions